The diagnosis, evaluation and treatment of acute and recurrent pediatric urinary tract infections. Issue 1 (January 2014) - Becknell, Brian; Schober, Megan; Korbel, Lindsey; Spencer, John David
<x xml:space="preserve">Abstract</x> Urinary tract infection (UTI) is one of the most common bacterial infections encountered by pediatricians. Currently, the diagnosis and management of acute UTI and recurrent UTI in children remain controversial. Recently published guidelines and large clinical trials have attempted to clarify UTI diagnostic and management strategies. In this manuscript, we review the diagnosis and management of acute and recurrent UTI in the pediatric population.